Pharmacogenomics of methotrexate and candidate genes in patients with idiopathic arthritis - I. I. Nazarchuk; V. V. Strogij; O. N. Volkova (Military Medicine, 2026)
Th i s ar t icle pro v i d es a comprehensive review of genetic factors that influence the pharmacokinetics and effects of methotrexate (MTX) in the treatment of juvenile idiopathic arthritis (JIA). It focuses on key genes and polymorphisms associated with MTX metabolism and transport, as well as their impact on the efficacy and tolerability of MTX therapy. The aim of the study is to review the results of genetic studies aimed at finding markers that can influence individual differences in the pharmacokinetics of MTX; to characterize the most well-studied genes involved in the pharmacogenomics of MTX and candidate genes in patients with JIA. The article analyzes the results of genetic studies published by leading international professional communities of specialists in this field. Information was searched in the PubMed and eLibrary networks.RU, Google Scholar, ClinPGx, by keywords.